ai làm cho , mình cho hay nhât

Question

ai làm cho , mình cho hay nhât
ai-lam-cho-minh-cho-hay-nhat

in progress 0
Hưng Gia 1 year 2020-11-04T07:27:36+00:00 2 Answers 59 views 0

Answers ( )

    0
    2020-11-04T07:28:52+00:00

    Đáp án:

     

    Giải thích các bước giải:

    1) x + 7 = 17

         x       = 17-7

         x       = 10

    2)  21 – x = 5

          x        = 21-5

          x         =16

    3)   7 + 2 x =27

             9     x =27

            x         = 27:9

            x         = 3

    4)  16 + 3 x = 36

            19    x  = 36

             x         = 36:19

             x         =  De SAI

     

    0
    2020-11-04T07:29:21+00:00

    Đáp án:

    12) x=11

    Giải thích các bước giải:

    \(\begin{array}{l}
    1)x + 7 = 17\\
     \to x = 10\\
    4)16 + 3x = 36\\
     \to 3x = 20\\
     \to x = \dfrac{{20}}{3}\\
    7)10 + 2x = \dfrac{{{4^5}}}{{{4^3}}}\\
     \to 10 + 2x = {4^2}\\
     \to 10 + 2x = 16\\
     \to 2x = 6\\
     \to x = 3\\
    10)185 – 3x + 15 = 5.16\\
     \to 200 – 3x = 80\\
     \to 3x = 120\\
     \to x = 40\\
    13)7x – 24 = \dfrac{{{5^6}}}{{{5^4}}}\\
     \to 7x – 24 = {5^2}\\
     \to 7x – 24 = 25\\
     \to 7x = 49\\
     \to x = 7\\
    16){3.2^x} = 48\\
     \to {2^x} = 16\\
     \to {2^x} = {2^4}\\
     \to x = 4\\
    2)21 – x = 5\\
     \to x = 16\\
    5)3x – 15 = 75\\
     \to 3x = 90\\
     \to x = 30\\
    8)160 – x – 2 = \dfrac{{{8^5}}}{{{8^3}}}\\
     \to 158 – x = {8^2}\\
     \to 158 – x = 64\\
     \to x = 94\\
    11)23x – 21 = \dfrac{{{5^6}}}{{{5^4}}}\\
     \to 23x – 21 = {5^2}\\
     \to 23x – 21 = 25\\
     \to 23x = 46\\
     \to x = 2\\
    14)x – 20 = 40.5\\
     \to x – 20 = 200\\
     \to x = 220\\
    3)7 + 2x = 27\\
     \to 2x = 20\\
     \to x = 10\\
    6)72 – 35 – x = 27\\
     \to 37 – x = 27\\
     \to x = 10\\
    9)2x – 6 – 12 = 10\\
     \to 2x – 18 = 10\\
     \to 2x = 28\\
     \to x = 14\\
    12)x + 19 = 30\\
     \to x = 11
    \end{array}\)

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )